Clinical mental health measures and prediction of postconcussion musculoskeletal injury - Buckley, T. A.; Bryk, K. N.; Enrique, A. L.; Kaminski, T. W.; Hunzinger, K. J.; Oldham, J. R. (Journal of Athletic Training, 2023)
Context The rate of lower extremity musculoskeletal injury (LE MSK) is elevated after concussion; however, the underlying mechanism has not been elucidated. Physical characteristics have been investigated despite poorer mental health being a common postconcussion complaint and linked to MSKs.